Severe type I interferonopathy and unrestrained interferon signaling due to a homozygous germline mutation in STAT2 - Duncan, Christopher J A; Thompson, Benjamin J; Chen, Rui; Rice, Gillian I; Gothe, Florian; Young, Dan F; Lovell, Simon C; Shuttleworth, Victoria G; Brocklebank, Vicky; Corner, Bronte; Skelton, Andrew J; Bondet, Vincent; et al. (Science immunology, 2019)
Excessive type I interferon (IFNα/β) activity is implicated in a spectrum of human disease, yet its direct role remains to be conclusively proven. We investigated two siblings with severe early-onset autoinflammatory disease and an elevated IFN signature. Whole-exome sequencing revealed a shared homozygous missense Arg148Trp variant in , a transcription factor that functions exclusively downstream of innate IFNs. Cells bearing STAT2 in homozygosity (but not heterozygosity) were hypersensitive to IFNα/β, which manifest as prolonged Janus kinase-signal transducers and activators of transcription (STAT) signaling and transcriptional activation. We show that this gain of IFN activity results from the failure of mutant STAT2 to interact with ubiquitin-specific protease 18, a key STAT2-dependent negative regulator of IFNα/β signaling. These observations reveal an essential in vivo function of STAT2 in the regulation of human IFNα/β signaling, providing concrete evidence of the serious pathological consequences of unrestrained IFNα/β activity and supporting efforts to target this pathway therapeutically in IFN-associated disease.